2009
DOI: 10.1111/j.1600-0528.2009.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of fluoride intake with children’s bone measures at age 11

Abstract: Background Relationships between fluoride intake and bone health continue to be of interest, as previous studies show conflicting results. Objectives The purpose is to report associations of fluoride intake with bone measures at age 11. Methods Subjects have been participating in the ongoing Iowa Fluoride Study/Iowa Bone Development Study. Mothers were recruited postpartum during 1992–95 from eight Iowa hospitals, and detailed fluoride questionnaires were sent every 1.5–6 months. From these, combined fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 28 publications
5
21
1
Order By: Relevance
“…Our results are consistent with several ecological studies (i.e., studies that did not assess fluoride intakes at the individual level, but instead compared bone measures among children living in communities with fluoridated versus non‐fluoridated water) which found no significant differences in bone outcomes by fluoridation status . Furthermore, a previous analysis of the IFS/IBDS data showed only modest relationships between DXA scans of hip, spine, and whole body and fluoride intakes at age 11 , with even weaker associations with DXA outcomes at age 15 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with several ecological studies (i.e., studies that did not assess fluoride intakes at the individual level, but instead compared bone measures among children living in communities with fluoridated versus non‐fluoridated water) which found no significant differences in bone outcomes by fluoridation status . Furthermore, a previous analysis of the IFS/IBDS data showed only modest relationships between DXA scans of hip, spine, and whole body and fluoride intakes at age 11 , with even weaker associations with DXA outcomes at age 15 .…”
Section: Discussionsupporting
confidence: 91%
“…A recent cohort study of South African adolescents reported a significant positive association of higher water fluoride (3 ppm versus 0.19 ppm) and radius BMD measured with the Norland single energy ( 125 I) photon absorptiometer in the 14‐year to 15‐year age group, but not in those 10–11 years old . Finally, we found no significant relationships between age 11 DXA bone measures of the hip, lumbar spine, and whole body and fluoride intake from birth to 3, 3–6, 6–8.5, 8.5–11 years, and cumulatively to 8.5 and 11 years .…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Most focused on comparing adults living in fluoridated vs nonfluoridated communities. Very few have investigated the effects of fluoride on bone characteristics in children/adolescents …”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50% of the absorbed fluoride remains associated with hard tissues, whereas all of the remainder is excreted in urine [4][5][6]. It distributes evenly throughout intracellular and extracellular spaces.…”
Section: Introductionmentioning
confidence: 99%